Estudo de propriedades mecânicas do grafeno por primeiros princípios - Erik de Oliveira Martins (2014)
The goal of this work is a theoretical study on mechanical properties of monolayer graphene, using as tool the density functional theory (DFT). We submit the graphene sheet to uniaxial tension along armchair and zigzag directions. We analyze the behavior of the stress-strain curve in the elastic limit. We also show that in the linear regime of the stress-strain curve the obtained values are very accurate for the Young's modulus. We also present an analysis of the Poisson ratio as a function of strain in the armchair and zigzag directions. Our calculations are in good agreement with experiments, and we conclude that the density functional theory is an excellent tool for the study of mechanical properties of graphene.